(untitled) (Historia, 2021)
1. R. Floud: An Introduction to Quantitative Methods for Historians 2. J. A. Faber: Drie eeuwen Friesland 3. E. M. W. Tillyard: The Elizabethan World Picture 4. C. H. Price: George Rex, King or Esquire? 5. B. B. Cohen: Writing about Literature 6. B. Kearney: Architecture in Natal from 1824 tot 1893 7. M. C. Kitshoff: Gottlieb Wilhelm Antony van der Lingen 8. E. C. Tabler: Pioneers of South West Africa and Ngamiland 9. H. Levin: The Myth of the Golden Age in the Renaissance 10. Van Stamverwante Bodem deur dr. J. Ploeger